STUDI NUMERIK EFEK LETAK AIR SUPPLY DIFFUSERS DAN AIR RETURN GRILLES PADA DISTRIBUSI TEMPERATUR DAN KECEPATAN UDARA DI BUS - Fauzun, Fauzun; Hidayat, Akbar Fadhlurrohman; Yogiswara, Cahyo Wibi (Jurnal Rekayasa Mesin, 2024)
The purpose of air conditioning system in the vehicle is to provide comfort for passengers. To achieve this, it is required to investigate the air flow and temperature distribution in the passenger area. This study aims to find the effect of layout variations of the air supply diffuser and air return grille on the temperature and velocity distribution in the passenger compartment of a bus and get the most optimal system with CFD simulation method that used ANSYS Fluent. The number of layout variations that simulated is six. The results can be inferred that the variation with one air supply diffuser at the floor or sidewall and the air return grille located on the bottom sidewall will result in lower temperature distribution. Then, it will make lower average air velocity at the top of the compartment. Considering nonuniformity index and heat removal efficiency, the most optimal scheme system is owned with one air supply diffuser on the sidewall, another on the ceiling, and the air return grille on the bottom sidewall.